Inhibition of cold‐welding and adhesive wear occurring on surface of the 6061 aluminum alloy by graphene oxide/polyethylene glycol composite water‐based lubricant. (6th December 2021) - Chen, Lu; Tu, Nan; Wei, Qianyang; Liu, Tao; Li, Chengzhi; Wang, Wenbo; Li, Jianhui; Lu, Hailin
Abstract : In this paper, graphene oxide/polyethylene glycol (GO/PEG) composite water‐based lubricant was prepared by an ultrasonic dispersion method, and characterized and analyzed by Fourier transform infrared (FT‐IR), Raman spectroscopy, X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA). The suspension performance of GO/PEG composite water‐based lubricant in water was verified by static sedimentation and centrifugation, and then, the prepared GO/PEG composite water‐based lubricant was added into 304 stainless steel and 6061 aluminum alloy, and the coefficient of friction (COF) curve, average COF value, average wear rate, corresponding photomicrographs of balls and disks after wear, and energy‐dispersive spectrometer (EDS) elemental analysis were used to illustrate the lubrication effect and lubrication mechanism. The results show that the GO/PEG composite water‐based lubricant possesses excellent suspension ability in water, and the average COF value and wear rate of GO/PEG composite water‐based lubricant are reduced by 78.8% and 88.8%, respectively, compared with water lubrication. The excellent lubrication effect of GO/PEG composite water‐based lubricant can effectively reduce the cold‐welding and adhesive wear phenomenon, mainly because GO/PEG composite water‐based lubricant first fills the uneven surface of friction mating to form a high‐quality lubricating film and then because of the special space structure of GO and the low shear between GO layers and the synergistic lubrication effect of GO/PEG.